Evaluation of Factors Affecting Return to Work Following Carpal Tunnel Release: A Statewide Cohort Study of Workers' Compensation Subjects - Anderson, Joshua T.; Stephens, Andrew R.; Haas, Arnold R.; Ahn, Nicholas U.; Kazmers, Nikolas H. (The Journal of hand surgery (American ed.), 2022)
Most randomized trials comparing open carpal tunnel release (OCTR) to endoscopic carpal tunnel release (ECTR) are not specific to a working population and focus mainly on how surgical technique has an impact on outcomes. This study’s primary goal was to evaluate factors affecting days out of work (DOOW) following carpal tunnel release (CTR) in a working population and to evaluate for differences in medical costs, indemnity payments, disability ratings, and opioid use between OCTR and ECTR with the intent of determining whether one or the other surgical method was a determining factor. Using the Ohio Bureau of Workers’ Compensation claims database, individuals were identified who underwent unilateral isolated CTR between 1993 and 2018. We excluded those who were on total disability, who underwent additional surgery within 6 months of their index CTR, including contralateral or revision CTR, and those not working during the same month as their index CTR. Outcomes were evaluated at 6 months after surgery. Multivariable linear regression was performed to evaluate covariates associated with DOOW. Of the 4596 included participants, 569 (12.4%) and 4027 (87.6%) underwent ECTR and OCTR, respectively. Mean DOOW were 58.4 for participants undergoing OCTR and 56.6 for those undergoing ECTR. Carpal tunnel release technique was not predictive of DOOW. Net medical costs were 20.7% higher for those undergoing ECTR. Multivariable linear regression demonstrated the following significant predictors of higher DOOW: preoperative opioid use, legal representation, labor-intensive occupation, increasing lag time from injury to filing of a worker’s compensation claim, and female sex. Being married, higher income community, and working in the public sector were associated with fewer DOOW. In a large statewide worker’s compensation population, demographic, occupational, psychosocial, and litigatory factors have a significant impact on DOOW following CTR, whereas differences in surgical technique between ECTR and OCTR did not. Therapeutic III.